Mezcal Production in Mexico: Between Tradition and Commercial Exploitation - Arellano-Plaza, Melchor; Paez-Lerma, Jesús Bernardo; Soto-Cruz, Nicolás Oscar; Kirchmayr, Manuel R.; Gschaedler Mathis, Anne (Frontiers in Sustainable Food Systems, 2022)
Mezcal is a traditional iconic Mexican distilled beverage obtained from varied species of agaves. Regardless of the area of production, the process always consists of five stages: harvesting the agaves, cooking, crushing, fermentation, and distillation. It is produced in a large area of Mexican territory, a large part of which is protected by the Denomination of Origin mezcal (DOM). Over time, the word mezcal has evolved from a generic name to a more specific term used to describe the agave-distilled beverages produced in the territory protected by the DOM under the Mexican official standard NOM-070-SCFI-2016 which defined Mezcal as a “Mexican distilled alcoholic beverage, 100% from maguey or agave, obtained by distillation of fermented juices with spontaneous or cultivated microorganisms, extracted from mature heads of maguey or cooked agaves, harvested in the territory covered by the DOM.” In the last 10 years, official production has increased, from <1 million liters in 2011 to almost 8 million liters. This substantial increase in production puts a lot of pressure on resources, in particular raw material, as part of the production is obtained from wild agave. On the other hand, it exposes tradition at risk by increasing production by modernizing production processes and sacrificing the artisanal aspect of this production. We consider appropriate to address the issue of sustainability in this context of great tradition and growing market demand. The article presents the relevant aspects of mezcal production, highlighting some particularities specific to certain production areas, it also addresses the problem of the official standard. A broad discussion is presented on the sustainability of artisanal processes, and the main points to be taken care of in this framework. Additionally, some elements considered as fundamental in the perspective of the design of a sustainable artisanal distillery are described. In summary, this article aims to review the current state of mezcal production, how sustainability may be addressed in a very artisanal process and what are the challenges of the production chain to satisfy an increase in demand without sacrificing the tradition and culture related to this iconic Mexican beverage.